Effect of ocean acidification on the oxygen consumption of the sea urchins Paracentrotus lividus (Lamarck, 1816) and Arbacia lixula (Linnaeus, 1758) living in CO2 natural gradients - Robert Fernández-Vilert; Robert Fernández-Vilert; Vanessa Arranz; Vanessa Arranz; Marta Martín-Huete; Marta Martín-Huete; José Carlos Hernández; Sara González-Delgado; Sara González-Delgado; Rocío Pérez-Portela; Rocío Pérez-Portela (Frontiers in Marine Science)
Ocean acidification (OA) stands out as one of the main threats to marine ecosystems. OA leads to a reduction in the availability of carbonate ions, which are essential for marine calcifiers such as echinoderms. We aim to understand the physiological responses of two sea urchin species, Paracentrotus lividus and Arbacia lixula to low pH conditions and determine whether their responses result from phenotypic plasticity or local adaptation. The study is divided into two parts: plasticity response over time, measuring respiration rates of individuals from the Mediterranean Sea exposed to low pH over seven days, and adaptation and plasticity under changing pH, analyzing individuals inhabiting a pH gradient in a natural CO2 vent system located in La Palma Island, Spain. Over the seven days of low pH exposure, distinct patterns in respiration rates were revealed, with both species demonstrating potential for acclimatization. Notably, P. lividus and A. lixula displayed unsynchronized acidosis/alkalosis cycles, suggesting different physiological mechanisms. Additionally, environmental history seemed to influence adaptive capacity, as specimens from fluctuating pH environments exhibited respiration rates similar to those from stable environments with heightened phenotypic plasticity. Overall, our results suggest that both species possess the capacity for metabolic plasticity, which may enhance their resilience to future OA scenarios but likely involve energetic costs. Moreover, CO2 vent systems may serve as OA refugia, facilitating long-term survival. Understanding the plastic responses versus adaptations is crucial for predicting the effects of OA on species distribution and abundance of marine organisms in response to ongoing climate change.